2015
DOI: 10.3899/jrheum.140429
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Total Contact Insoles in Patients with Plantar Fasciitis

Abstract: A TCI can be used to reduce pain while walking and to increase walking distance in individuals with PF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 23 publications
3
64
1
3
Order By: Relevance
“…Similar results were found in the study that could not be pooled for short-term function 21. One study reported on midterm function and found no difference between both interventions 19. One study reported on function at long term and found no significant difference15 (online supplementary file 3).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results were found in the study that could not be pooled for short-term function 21. One study reported on midterm function and found no difference between both interventions 19. One study reported on function at long term and found no significant difference15 (online supplementary file 3).…”
Section: Resultssupporting
confidence: 76%
“…Data on short-term pain were pooled for all three studies, and no significant difference was found ((SMD 0.22 (95%CI −0.05 to 0.50))I 2 0%) between sham and custom-made orthoses (online supplementary file 6). One study reported pain at midterm and no difference was found between both interventions 19. One study reported pain at long term and no difference was found15 (online supplementary file 3).…”
Section: Resultsmentioning
confidence: 95%
“…In the longer term , this study found very-low-quality evidence to low-quality evidence that foot orthoses are not effective at reducing pain or improving function. Only two trials had data that could be pooled for meta-analysis, and they had different endpoints, with one ending at 6 months25 and the other at 12 months 26…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the different findings between the Rasenberg et al 1 systematic review and our systematic review2 is the outcome measure for pain that was selected from one trial, by Oliveira et al ,3 for the comparison of customised foot orthoses to sham orthoses. In the Rasenberg et al 1 review, the authors chose to extract data from the Foot Health Status Questionnaire pain subscale, whereas for our review,2 we chose to extract the outcome measure from each trial that was the primary outcome (if specified by the authors of each included trial), and therefore we extracted pain with activity measured using the visual analogue scale (VAS).…”
mentioning
confidence: 89%
“…In the Rasenberg et al 1 review, the authors chose to extract data from the Foot Health Status Questionnaire pain subscale, whereas for our review,2 we chose to extract the outcome measure from each trial that was the primary outcome (if specified by the authors of each included trial), and therefore we extracted pain with activity measured using the visual analogue scale (VAS). Although Oliveira et al 3 did not prespecify a primary outcome measure, they used the VAS to justify their sample size, and on this basis, we considered VAS to be the primary outcome, which we still believe is appropriate.…”
mentioning
confidence: 99%